Essential Facilities der Eisenbahninfrastruktur. Eine ökonomische und juristische Begriffsabgrenzung. - Ott, Anselm (Deutscher Verkehrs-Verl., 2006)
Seit einigen Jahren ist auch in Europa der Begriff der "Essential Facility" im Bereich von Netzindustrien allgegenwärtig. Eine Essential Facility ist eine Einrichtung, die aus ökonomischen oder rechtlichen Gründen nicht dupliziert werden kann, die aber nötig ist, um auf einem parallelen, vor- oder nachgelagerten Markt Geschäfte durchzuführen. difu

In most European countries discrimination-free use of transport infrastructure has been discussed in recent years. As a result of this discussion, European legislation and regulation is now enforcing the open access of (rail) infrastructure. The right to use infrastructure assets by any third party has been granted by several European directives. Despite this improvement, there are still severe entrance barriers for new providers. The focus of this paper is on the essential facility doctrine. A number of court decisions underline a wide use of this doctrine, not only on the core of infrastructure (use of ports, tracks etc.). There are also points of views, which go beyond these applications. The importance of this doctrine for discrimination-free access to infrastructure related services is currently discussed widely and it is shown that the doctrine should be used in a broad context. The emphasis of the paper is on rail infrastructure. difu
Keywords: Öffentlicher Verkehr; Wettbewerb; Schienenverkehr; Eisenbahn; Verkehrsinfrastruktur; Technische Infrastruktur; Rechtsprechung; Netzzugang; Marktöffnung; Deregulierung